2019
DOI: 10.4314/mmj.v31i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Presenting features and treatment outcomes of chronic lymphocytic leukaemia in a resource poor Southern Nigeria

Abstract: Background Chronic lymphocytic leukaemia is a relatively common haematological malignancy affecting older adults, accounting for about 20% of haematological malignancies in Nigeria. Diagnosis of this disease depends on the demonstration of clonal lymphocytosis > 5 × 109/L with a characteristic immunophenotypic pattern amidst other clinical and laboratory features. Objectives To determine the predominant clinical and laboratory features of CLL at presentation and their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…Our study also showed male preponderance [ Figure 1 ] which is similar to the finding by Madu et al . and other study outside Africa[ 10 ] but varies with the finding of Salawu et al . and Omoti et al .…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Our study also showed male preponderance [ Figure 1 ] which is similar to the finding by Madu et al . and other study outside Africa[ 10 ] but varies with the finding of Salawu et al . and Omoti et al .…”
Section: Discussioncontrasting
confidence: 56%
“…There is also a report of male preponderance worldwide,[ 9 ] this is in keeping with a study by Madu et al . [ 10 ] but varies with the finding of Salawu et al . [ 11 ] which reported the female preponderance.…”
Section: Introductionmentioning
confidence: 70%
“… 1 , 2 , 14 More than half of our patients with CLL were young (< 55 years) compared with those in the United States and Europe where only about 5%-11% of cases are younger than 55 years. 14 , 15 Although the epidemiology of CLL both in Nigeria and globally generally shows a male predominance, 16 our study showed a slight female preponderance. A female preponderance has also been reported in our environment.…”
Section: Discussionmentioning
confidence: 48%
“…Administration protocol for treatment of CLL consist of combination of immunotherapy and standard chemotherapy for patients with symptomatic, advanced or progressive disease. While for patients with stable disease the "watch and wait" algorithm is usually deployed (Hallek et al, 2018), (Madu et al, 2019) .…”
Section: Introductionmentioning
confidence: 99%